PENGARUH EKSTRAK DAUN PEGAGAN (Centella asiatica) TERHADAP SIKLUS ESTRUS MENCIT (Mus musculus L) DAN SUMBANGANNYA TERHADAP PEMBELAJARAN BIOLOGI SMA - Verly Tria Darma; Lucia Maria Santoso; Riyanto Riyanto (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2017)
Abstract:The aimed of this study is to analyze the effect of Pegagan leaf extract  to the estrous cycle of mice. The method was implemented is the experimental method of Randomized Complete Design ( RCD), which used twenty four  female mice. The study consisted three group of treatment with eight replications. Treatment for the provision of Pegagan leaf extract with doses of 0 mg / 10 g body weight (BW) , 2 mg / 10 g BW , and 8 mg / 10 g BW. Pegagan leaf extract given to the mice by gavage for 3 days. Parameters measured were cytological picture of vaginal smears and the duration of the estrous cycle in the female mice. Total average length of the estrous cycle in mice P0 , P1 and P2 were 4.5 days, 5.75 days, and 4.62 days. The results showed that the leaf extract of Pegagan with a dose of 2 mg / 10 g BW maximum increase the duration of estrus cycle time in mice. The increasing of the estrous cycle time because of the phase proestrus and estrus of the mice experienced an increasing of time. The results of the studywere expected to be an additional material as well as additional information on the Learning Sciences School (SMA) X class the second semester on Subject Matter Kingdom Plantae basic competency 3.3 of Describing Characteristics Divisio in the World of Plants and Role for Survival on earth. Keywords : estrous cycle, mice (Mus musculus L), ovulation , pegagan (Centella asiatica).